Adjuvant EGFR-TKIs for Patients With Resected EGFR-Mutant Non-Small Cell Lung Cancer: A Meta-Analysis of 1,283 Patients - Chen, Rui-Lian; Sun, Ling-Ling; Cao, Yang; Chen, Han-Rui; Zhou, Jing-Xu; Gu, Chu-Ying; Zhang, Ying; Wang, Si-Yu; Hou, Wei; Lin, Li-Zhu (Frontiers in Oncology, 2021)
Background Cisplatin-based chemotherapy was previously considered as the standard adjuvant therapy for improved overall survival (OS) in patients with non-small cell lung cancer (NSCLC) after surgery. However, the benefit was limited due to high risks of recurrence and adverse events. In the present study, the efficacy of adjuvant epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) for EGFR-mutant patients after surgery was investigated using the latest updated data. Methods This meta-analysis included a comprehensive range of relevant studies identified from databases searches. Disease-free survival (DFS) and OS with hazard ratios (HRs) were calculated using random-effect or fixed-effect models. Subgroup analysis was also performed. Results A total of seven randomized clinical trials were included in the meta-analysis, and involved 1,283 NSCLC patients harboring EGFR mutations. In resected EGFR-mutant NSCLC patients, adjuvant EGFR-TKIs were significantly better than chemotherapy in terms of DFS (HR: 0.41; 95%CI: 0.24–0.70, P = 0.001), without showing any benefit in OS (HR: 0.72; 95%CI: 0.37–1.41, P = 0.336). No significant difference in DFS was observed between patients with EGFR exon 19 deletion and those with L858R mutation. Resected EGFR-mutant NSCLC patients treated with osimertinib experienced improved DFS and a lower risk of brain recurrence than those treated with gefitinib or erlotinib. Adjuvant EGFR-TKIs reduced the risk of bone and lung relapse, without decreasing the risk of local recurrence and liver relapse. Conclusion This meta-analysis shows that adjuvant EGFR-TKI therapy could significantly prolong DFS in patients with resected EGFR-mutant NSCLC. Treatment with osimertinib showed improved DFS with a lower risk of brain recurrence than treatment with gefitinib or erlotinib for resected disease.